The National Evaluation Policy landscape in Africa: A comparison - Takunda, Chirau; Cara, Waller; Caitlin, Blaser Mapitsa (CLEAR-AA, 2018)
This policy brief examines key elements of national evaluation policies among selected African countries with a view to inform policy-makers on good practices for the development of such policies. This brief draws from a comparative study conducted by CLEAR-AA in 2018 of the status of national evaluation policies of South Africa, Nigeria, Zimbabwe, Uganda, and Kenya.
Keywords: The National Evaluation Policy landscape in Africa: A comparison; National Evaluation Policy landscape in Africa